Pore structure characterization of low-permeability sandstone by dual LNMR T2 cutoff values: a case study of the fourth member of shahejie formation, dongying sag, jiyang depression - Wang, Min; Chen, Kang; Geng, Bin; Liang, Qiang (Frontiers in Earth Science, 2025)
Low-permeability sandstone reservoirs usually exhibit complex pore structure characteristics that significantly controls the type of fluid in the pore space and its occurrence and seepage mechanisms. In this work, the mercury injection capillary pressure (MICP) and low-field nuclear magnetic resonance (LNMR) analyses were conducted on low-permeability sandstone samples collected from the fourth member of the Eocene Shahejie Formation (Es4) of Dongying sag to characterize the pore structure, analyze the relationship between dual LNMR T2 cutoff values and the pore fluid type, and discuss the role of dual LNMR T2 cutoff values on the pore structure characterization. The results (1) indicated that the pore structure of low-permeability sandstones in the study area exhibits strong heterogeneity and can be divided into three types based on the MICP and LNMR results. Typically, sandstone samples with a type I pore structure usually exhibits characteristics such as low displacement pressure (Pd), large average pore throat radius, and a wide distribution of pore size. (2) shown that the dual LNMR T2 cutoff values can better characterize the occurrence of fluids in sandstone samples in the study area. When T2 >T2C2, fluid in the pore space is fully moveable; conversely, when T2<T2C2, fluid becomes completely immobile. The T2C1 and T2C2 range from 0.16 to 3.37 ms and from 17.34 to 346.78 ms, respectively. (3) found that fractal dimensions derived from LNMR curves under dual LNMR T2 cutoff values provide a more precise characterization of pore structure heterogeneity in low-permeability sandstone reservoirs compared to a single fractal dimension. When T2>T2C1, pores demonstrate fractal characteristics, enabling the representation of pore structure heterogeneity through fractal dimensions. Specifically, samples with Type I pore structures tend to show the smallest D2 and D3 values. In generally, by applying dual T2 cutoffs (T2C1 and T2C2) to LNMR-derived fractal dimensions, the pore structure of low-permeability sandstones can be better characterized, facilitating more accurate reservoir effectiveness assessments for oil and gas exploration.